Price Determination of Agricultural Insurance Premium Based on Rainfall Index With Black-Scholes Model - Aditya Prasetyo, Dimas; Setiawan, Luki (Operations Research: International Conference Series, 2020)
This article discusses the use of the Black-Scholes model to calculate the price of agricultural insurance premiums based on the rainfall index. The Black-Scholes model is one of the models used to determine option prices. The research method used is studying the material through mathematics books and journals and collecting secondary data. The data used in this study are rainfall data and rice production data in Magelang City from 2019 to 2020. Based on the results and discussion, the quarterly rainfall data that has a strong correlation are quarterly rainfall one and three. For the reference size with the latest rainfall data (319.5 mm) the premium obtained is IDR 3,557,321.00 per hectare, while for the reference size with the average rainfall data (1094,725 mm) the premium obtained is IDR 623,387. ,00 per hectare. Based on the calculation results, the higher the percentile value, the higher the premium value for the two reference sizes.